Current challenges of unresectable stage III NSCLC: are we ready to break the glass ceiling of the PACIFIC trial?. (July 2022) - Remon, Jordi; Levy, Antonin; Singh, Pawan; Hendriks, Lizza E. L.; Aldea, Mihaela; Arrieta, Oscar
Consolidation anti-programmed death-ligand 1 has become a new standard of care in unresectable stage III non-small cell lung cancer (NSCLC) following chemo-radiotherapy (CTRT), based on the results of two phase III trials. Advances remain however needed, in particular to reduce the risk of distant relapse and for treatment personalization. Newer strategies are currently being tested, including consolidation with dual immune checkpoint inhibitors (ICIs), concurrent chemo-radioimmunotherapy and (chemo)-immunotherapy induction before CTRT. One randomized phase II reported better outcomes with a double ICI consolidation as compared with durvalumab alone. Three nonrandomized phase II trials also suggested that concurrent ICI-CTRT was feasible. Within this review, we summarize the current evidence, highlight ongoing trials and discuss challenges that will ideally lead to a cure for more patients with unresectable stage III NSCLC.